2022
DOI: 10.24136/eq.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Did the COVID-19 pandemic amplify the positive impact of income diversification on the profitability of European banks?

Abstract: Research background: The contribution of banks? non-interest income to the total income becomes particularly important in the face of a severe financial crisis, usually accompanied by burdensome restrictions in economic activity, insolvencies of enterprises and households and low interest rates of central banks. Purpose of the article: This study investigates banks in 40 European countries to determine whether non-interest income had a significant impact on the bank?s profitability and whether the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Banks also had to address this problem, which put pressure on the people (Caby et al 2022) who wanted to profit despite the bad economy. European banks were discussed by Kozak and Wierzbowska (2022). Asian banks were analyzed by Nguyen and Le (2022) and Dsouza et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Banks also had to address this problem, which put pressure on the people (Caby et al 2022) who wanted to profit despite the bad economy. European banks were discussed by Kozak and Wierzbowska (2022). Asian banks were analyzed by Nguyen and Le (2022) and Dsouza et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To increase bank profitability during the pandemic, Kozak and Wierzbowska (2022) emphasizes that banks need to increase non-interest income. The impact of the COVID-19 pandemic explained by Ghosh and Saima (2021) will be more pronounced in banks with low levels of capital adequacy, liquidity, and performance as well as high non-performing loans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means that revenue diversification does not help banks to be more stable. Also, Kozak and Wierzbowska (2022) tested the impact of income diversification on banks' profitability, furthermore, they examined whether the severity of the COVID-19 pandemic affects the relationship between income diversification and profitability. The study relied on a sample consisting of forty European banks over the period from 2019 to 2020.…”
Section: ‫ديسمبر‬ ‫الثانى‬ ‫العدد‬ ‫عشر‬ ‫الرابع‬ ‫المجلد‬ ‫واإلدارية...mentioning
confidence: 99%
“…On the other hand, some studies found that the effect of business diversification on banks' risks was negative (e.g., Sissy et al, 2017;Ovi et al, 2020;Li et al, 2021;Alouane et al, 2022;Ochenge, 2022). Regarding performance, some studies showed that business diversification positively affected banks' performance (e.g., Ferreira et al, 2019;Li et al, 2021;Uddin et al, 2021;Alouane et al, 2022;Kozak and Wierzbowska, 2022;Ochenge, 2022), while other studies implied that business diversification negatively affected banks' performance (e.g., Edirisuriya et al, 2015;Ngoc Nguyen, 2019). It is noteworthy that some studies demonstrated an insignificant impact on banks' performance (e.g., Edirisuriya et al, 2015); Raei et al, 2016;Abuzayed et al, 2018).…”
Section: ‫ديسمبر‬ ‫الثانى‬ ‫العدد‬ ‫عشر‬ ‫الرابع‬ ‫المجلد‬ ‫واإلدارية...mentioning
confidence: 99%
See 1 more Smart Citation